(untitled) (Conferencea, 2022)
Rational nutrition is one of the main factors in maintaining the health of children and adolescents, as well as their high performance and body resistance to adverse external influences. Nutrition is the only source of energy and plastic material that a person needs for life, and especially its adequacy and balance are necessary for a growing organism.